Comparison of the adverse events of preprandial and postprandial lasmiditan intake: A retrospective chart review - Yuu Tatsuoka; Tamae Naruse; Atsushi Shima; Ryosuke Takahashi; Yoshihisa Tatsuoka (Cephalalgia Reports)
Background Lasmiditan is suitable for the acute treatment of migraine in patients who are intolerant or unresponsive to triptans. However, lasmiditan can cause adverse events that affect treatment adherence. The effects of predose food consumption on the development of adverse events after lasmiditan intake remain unclear. Methods This single-center retrospective study included 23 patients who received both preprandial and postprandial lasmiditan and experienced adverse events. To determine whether meal timing influences these adverse events, we examined the differences in the severity of adverse events between preprandial and postprandial lasmiditan administration using medical records and patient-reported headache diaries. Results All 23 patients experienced adverse events such as somnolence, dizziness, disequilibrium, fatigue, and palpitations following preprandial lasmiditan intake. Postprandial administration of lasmiditan was associated with significantly lower severity and reduced odds of adverse events compared with preprandial administration ( p  < 0.001). Conclusion Our results suggest that postprandial lasmiditan intake may affect the incidence and severity of the adverse events.